Independent audit and non-economic factors affecting Vietnamese enterprises' enforced tax compliance behavior - Hong, Nguyen Thi Phuong; Hoa, Tran Thi (Nurture, 2024)
Purpose: The study aims to examine non-economic factors such as independent audit, tax knowledge, tax awareness, tax morale, tax system complexity, and corporate brand in relation to enforced tax compliance of enterprises in Ho Chi Minh City, Vietnam. Design/ Methodology/ Approach: The study used questionnaires collected from survey subjects who are accountants, chief accountants, or chief financial officers. There were 482 enterprises surveyed in Ho Chi Minh City, Vietnam. Findings: The research results have shown that there is no difference in enforced tax compliance behavior between enterprises with financial statements audited by Big 4 auditing companies and those with Big 4-audited financial statements. In addition, tax knowledge, tax awareness, and company brand have a positive impact on enforced tax compliance behavior. Meanwhile, tax system complexity has the opposite effect, and tax morale has no impact on the enforced tax compliance behavior of enterprises in Ho Chi Minh City, Vietnam. Conclusion: Based on this research, governments, tax authorities, and universities can come up with more suitable solutions to improve enterprises' enforced tax compliance behavior. Research Limitations: This study only tested the impact of independent audit and non-economic factors such as tax knowledge, tax awareness, tax morale, tax system complexity, corporate brand on ETC. Future studies can examine additional economic factors such as tax rates, tax penalties, tax audits, tax compliance costs, and ETC.